The role of government trust and responsiveness in shaping sustainable tourism in West Sumatera, Indonesia - Said, Zulkenedi; Syamsir, Syamsir (Publisher of Widyagama University of Malang (UWG Press), 2024)
The formulation of tourism policy has given rise to a plethora of policy concerns in the tourism sector, some of which may endure. The primary obstacles confronting the provinces of West Sumatra are a substantial reduction in the number of tourists, short-term closure of renowned tourist destinations, and attendant severe economic consequences. It is imperative that the government adopt effective policies to promote increased tourist visits to the region to mitigate these challenges. In certain locales of West Sumatra, the risk of overtourism may arise, which could have detrimental effects on the environment, cultural heritage, and way of life of the indigenous population. This studyused a descriptive method to elucidate the characteristics of the population and the phenomena being examined. The objective of quantitative research is to gather information that can be statistically analyzed using population samples. The study participants were tourists who had originated in West Sumatra. The multistage random sampling approach, which involves the use of two or more sampling techniques, was employed for the sampleselection. The findings of this study reveal that government trust, policy responsiveness, level of satisfaction with responses, and transparency of government information have significant impacts on tourism policy. Tourism has the potential to serve as a potent instrument for promoting global sustainability.JEL ClassificationÂ Q01; Z32; Z38To cite this article: Said, Z. & Syamsir. (2024). The role of government trust and responsiveness in shaping sustainable tourism in West Sumatera, Indonesia. Journal of Socioeconomics and Development, 7(1), 24-37. https://doi.org/10.31328/jsed.v7i1.5105